2020
DOI: 10.1007/s13178-020-00487-1
|View full text |Cite
|
Sign up to set email alerts
|

Heteronormativity in Italy: Psychometric Characteristics of the Italian Version of the Heteronormative Attitudes and Beliefs Scale

Abstract: Introduction Heteronormativity describes a hierarchical societal system that encompasses heterosexuality and binary gender identity as normal and natural, defining boundaries of acceptable heterosexuality and gender identity. As no comprehensive measures of heteronormativity exist in Italy, this study evaluated the psychometric characteristics of an Italian version of the Heteronormative Attitudes and Beliefs Scale (HABS), a measure assessing essential and binary beliefs about sex and gender and normative beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 105 publications
(132 reference statements)
3
10
0
Order By: Relevance
“…Habarth (2014) thus proposed that heteronormativity comprises two dimensions: Essentialist beliefs about the binary nature of sex and gender (Essentialism), and attitudes derived from these beliefs regarding expected behaviors of people as man or woman, individually and in relationships (Normative behavior). This two-dimensional structure of heteronormativity is supported by psychometric evidence from Italy (Scandurra et al, 2021) and Chile (Alarcón et al, manuscript under review). Other research has linked heteronormativity to personality traits (e.g., openness to experience), political attitudes (e.g., right-wing authoritarianism), sexual prejudice, and demographic variables such as sexual orientation and gender (Habarth, 2014;Habarth et al, 2019a,b;Ray and Parkhill, 2021;Scandurra et al, 2021).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Habarth (2014) thus proposed that heteronormativity comprises two dimensions: Essentialist beliefs about the binary nature of sex and gender (Essentialism), and attitudes derived from these beliefs regarding expected behaviors of people as man or woman, individually and in relationships (Normative behavior). This two-dimensional structure of heteronormativity is supported by psychometric evidence from Italy (Scandurra et al, 2021) and Chile (Alarcón et al, manuscript under review). Other research has linked heteronormativity to personality traits (e.g., openness to experience), political attitudes (e.g., right-wing authoritarianism), sexual prejudice, and demographic variables such as sexual orientation and gender (Habarth, 2014;Habarth et al, 2019a,b;Ray and Parkhill, 2021;Scandurra et al, 2021).…”
Section: Introductionmentioning
confidence: 61%
“…This two-dimensional structure of heteronormativity is supported by psychometric evidence from Italy (Scandurra et al, 2021) and Chile (Alarcón et al, manuscript under review). Other research has linked heteronormativity to personality traits (e.g., openness to experience), political attitudes (e.g., right-wing authoritarianism), sexual prejudice, and demographic variables such as sexual orientation and gender (Habarth, 2014;Habarth et al, 2019a,b;Ray and Parkhill, 2021;Scandurra et al, 2021). Further explorations of heteronormativity posit that its nature transcends the realm of sexuality and gender and involve other identity markers and life conditions such as family structure, socioeconomic status, and ethnic origin (Seal, 2019;Pollitt et al, 2021).…”
Section: Introductionmentioning
confidence: 61%
“…The minority stress theory (Meyer, 2003) postulated that sexual minorities experience unique stressors related to their sexual minority identity and negatively impact their health (Scandurra et al, 2020c(Scandurra et al, , 2021. Particularly, the minority stress theory distinguishes two types of stressors: distal stressors, which are external, such as prejudice or discriminatory events, and proximal stressors, which are internal stressors, negative internalized self-experiences such as internalized homophobia or transphobia, and psychological distress (Meyer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Heteronormativity has been strictly related to sexism and sexual stigma and in particular to homonegativity (HN), which is defined as negative attitudes toward sexual minorities based on monitoring divergence from traditional masculine and feminine roles (Habarth, 2015 ; Scandurra et al, 2020 ). López-Sáez et al ( 2020 ) found sexism and HN to be stronger, and resistance to heteronormativity to be lower, among groups higher in the gender hierarchy.…”
Section: Introductionmentioning
confidence: 99%